Diagnostic accuracy of neuroimaging in pediatric optic chiasm/sellar/suprasellar tumors. Issue 6 (8th March 2019) - Norris, Gregory A.; Garcia, Jacquelyn; Hankinson, Todd C.; Handler, Michael; Foreman, Nicholas; Mirsky, David; Stence, Nicholas; Dorris, Kathleen; Green, Adam L.
Abstract: Preoperative diagnosis for tumors arising in the optic chiasm/sellar/suprasellar region in children is helpful to determine surgical necessity and approach, given the high operative risk in this area. We evaluated the ability to differentiate tumor type by preoperative neuroimaging. Thirty‐eight of 53 tumors were correctly diagnosed by neuroimaging based on final pathologic diagnosis (prediction accuracy 72%). Prediction accuracies were 87% (20/23) for craniopharyngioma, 79% (11/14) for optic pathway glioma, 64% (7/11) for germ cell tumor, and 0% (0/5) for Langerhans cell histiocytosis. Diagnosis of optic chiasm/sellar/suprasellar tumors in children by imaging alone should be considered when biopsy is considered high risk.